2016
DOI: 10.1016/j.tig.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Connections: R-Loops and Chromatin Patterning

Abstract: RNA molecules such as long non-coding RNAs play critical roles in regulating gene expression, chromosome architecture, and the modification states of chromatin. Recent developments suggest that RNA may also influence gene expression and chromatin patterns through the interaction of nascent transcripts with their DNA template via the formation of co-transcriptional R-loop structures. R-loop formation over specific, conserved, hotspots occurs at thousands of genes in mammalian genomes and represents an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
178
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 110 publications
3
178
0
Order By: Relevance
“…Next we increased the GC-content in the R-loop sequences to test whether this would determine high affinity binding, since R-loops are predominantly formed at GC-rich genomic regions [35]. We have shown no binding or weak binding to sequences in the range from 0 to 25% CG content, identified strong binding to sequence with 52% CG content and weak binding to a sequence with 75% GC content (22GC75).…”
Section: Resultsmentioning
confidence: 99%
“…Next we increased the GC-content in the R-loop sequences to test whether this would determine high affinity binding, since R-loops are predominantly formed at GC-rich genomic regions [35]. We have shown no binding or weak binding to sequences in the range from 0 to 25% CG content, identified strong binding to sequence with 52% CG content and weak binding to a sequence with 75% GC content (22GC75).…”
Section: Resultsmentioning
confidence: 99%
“…Excessive R-loop formation may also result from defects in RNA export (Huertas and Aguilera, 2003) or pre-mRNA splicing (Li and Manley, 2005), indicating that the commitment of nascent RNA to co-transcriptional RNA-processing pathways in a timely manner helps prevent excessive R-loop formation in normal cells (Bonnet et al, 2017). Despite these advances, many pressing questions remain in understanding R-loop biology with respect to its formation and dynamics in relationship to regulated gene expression, especially at the genome scale (Chédin, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this affinity probe has been coupled with deep sequencing to detect R-loops genome-wide in yeast (Chan et al, 2014; El Hage et al, 2014; Wahba et al, 2016), plant (Xu et al, 2017), and mammals (Ginno et al, 2012, 2013; Nadel et al, 2015; Sanz et al, 2016; Stork et al, 2016). The majority of these methods use the S9.6 antibody to capture RNA/DNA hybrids from restriction digested genomic DNA followed by deep sequencing of captured DNA (DNA:RNA immunoprecipitation [DRIP] sequencing [DRIP-seq] and its derivatives) or RNA (DNA:RNA immunoprecipitation followed by cDNA conversion [DRIPc]-seq and its derivatives) (Chédin, 2016). Because of limited resolution with restriction digestion, additional efforts have also been made to use sonication to increase R-loop mapping resolution (Halász et al, 2017; Nadel et al, 2015); however, such treatment may destroy some fragile R-loops in the absence of fixation.…”
Section: Introductionmentioning
confidence: 99%
“…R-loops are widely mapped genome-wide by exploiting the strong affinity of the S9.6 antibody for DNA:RNA hybrids [5,6]. Recent maps have shown that R-loops can occupy between 5% and 10% of the genome in yeast, vertebrates and Arabidopsis thaliana [79].…”
Section: Introductionmentioning
confidence: 99%
“…However, a mounting body of evidence also suggests that R-loops play physiological roles in transcriptional control and chromatin patterning (reviewed in Refs. [1,2,5]). What distinguishes toxic and beneficial R-loops is still unclear.…”
Section: Introductionmentioning
confidence: 99%